A INDÚSTRIA DO AGRONEGÓCIO E AS PRÁTICAS DA SUINOCULTURA, À LUZ DA FORÇA NORMATIVA DA PROTEÇÃO DOS ANIMAIS NÃO HUMANOS - Weiss Gonçalves, Marina; Fazolli, Silvio Alexandre (Revista Brasileira de Direito Animal, 2022)
The main objective of this article is to analyze the practices of Brazilian pig farming and the mistreatment and cruelty exercised by the activity. Using the hypothetical-deductive method, the work addresses socio-environmental aspects that involve the agribusiness industry, especially the myth that only animal meat provides the necessary nutrients to the human body and the strength of agribusiness, an activity with significant participation in the economy. It brings the capitalist factors of production involved in swine farming and also analyzes the normative force that holds the protection of animals, in the light of the constitutional provisions contained in articles 170, VI and 225, §1, VII, CF, which ensure animals protection against cruel practices and observance, by the economic order, to the defense of the environment as a principle.